2005
DOI: 10.1088/1126-6708/2005/05/066
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of confinement in compact QED

Abstract: Compact U(1) lattice gauge theory in four dimensions is studied by means of an efficient algorithm which exploits the duality transformation properties of the model. We focus our attention onto the confining regime, considering the interquark potential and force, and the electric field induced by two infinitely heavy sources. We consider both the zero and finite temperature setting, and compare the theoretical predictions derived from the effective string model and the dual superconductor scenario to the numer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 74 publications
5
75
0
Order By: Relevance
“…[26,27] for a discussion) and obtain a simple spin model with global Z symmetry and integer-valued s variables, defined on the sites of the dual lattice (note that, in D = 3 + 1 dimensions, the same transformation leads to a model with local Z symmetry [28][29][30][31][32]). More precisely, the duality transformation is an exact map of the original partition function to…”
Section: Duality Transformationmentioning
confidence: 99%
“…[26,27] for a discussion) and obtain a simple spin model with global Z symmetry and integer-valued s variables, defined on the sites of the dual lattice (note that, in D = 3 + 1 dimensions, the same transformation leads to a model with local Z symmetry [28][29][30][31][32]). More precisely, the duality transformation is an exact map of the original partition function to…”
Section: Duality Transformationmentioning
confidence: 99%
“…[47,48] and references therein, in terms of topologically non-trivial excitations which can be localized in elementary lattice cubes [49] and interpreted as magnetic monopoles. Numerical investigations [50] have revealed that such monopoles are responsible for the phase structure of the theory.…”
Section: Jhep06(2010)050mentioning
confidence: 99%
“…These results are displayed in Figure 2 (upper panel). We see the Coulomb potential above the transition, β = 1.05, and the linear rising potential below the phase transition, β = 1.0 (see also [31] for numerical investigations of the confining phase). In the lower panel of Figure 2 we have plotted the behaviour of the determinant det[M (r, t)].…”
Section: Numerical Resultsmentioning
confidence: 86%